"BEYOND PROFIT: THE ECONOMIC CASE FOR A GREEN REVOLUTION" - R. VENKATESH; M.GOPI (International Conference on Health Science, Green Economics, Educational Review and Technology, 2019)
The world is facing a major environmental crisis due to increased carbon emissions, pollution, and natural resource depletion. As a result, many countries and businesses have started to focus on implementing sustainable and green practices to reduce their impact on the environment. This paper examines the economic case for a green revolution, arguing that it can lead to significant benefits beyond just environmental sustainability, including increased profitability, innovation, and competitiveness. The paper also explores the challenges associated with implementing a green revolution and offers recommendations for businesses and policymakers.